2020
DOI: 10.3390/insects11120887
|View full text |Cite
|
Sign up to set email alerts
|

Olive Production Threatened by a Resurgent Pest Liothrips oleae (Costa, 1857) (Thysanoptera: Phlaeothripidae) in Southern Italy

Abstract: This study investigated a resurgence of Liothrips oleae Costa (Thysanoptera: Phlaeothripidae), an insect pest of olive crops, in a focal Southern Italian olive-producing area (Calabria Region). The young and adult olive thrips feed on the leaves and fruits of wild and cultivated olive trees, producing distortions, necrosis, and premature dropping of fruit. In our study, organic and integrated olive groves were compared for two years in order to establish the relationship between leaf and fruit damage among oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Figure 1 shows some of the most common types of physical symptoms observed on olive fruits. Only two studies have been conducted on thrips attacks on olive trees, which were conducted by Marullo and Vono [ 11 ] and Vono et al [ 28 ] in Italy. The authors observed the same symptoms on olive fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows some of the most common types of physical symptoms observed on olive fruits. Only two studies have been conducted on thrips attacks on olive trees, which were conducted by Marullo and Vono [ 11 ] and Vono et al [ 28 ] in Italy. The authors observed the same symptoms on olive fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Each survey area had a range of 3 hectares, and thrips in flowers were counted on 10 plants randomly selected from the three citrus crops. Following the protocol used by Vono et al [55] and Marullo et al [56], from each plant, 40 flowers randomly distributed from the outskirts of the canopy were collected from the different sectors of sun exposure: northeast (NE); southeast (SE); southwest (SW); and northwest (NW). Morphological identification of the specimens was carried out using the identification keys of Mound and Kibby [57] and Marullo [16], and the mounting of adult specimens of both sexes on microscope slides was carried out following the method described by Mound and Marullo [58] and Marullo [16].…”
Section: Study Sites and Thrips Sampling Monitoring Methods In Southe...mentioning
confidence: 99%
“…However, there seems to be no demonstration that this inhibits the growth of infested trees. Similar leaf damage is caused on persimmon trees (Diospyros kaki) in Japan by Ponticulothrips diospyrosi [17]; in southern Europe, Liothrips oleae is known to cause leaf distortions on olive trees [18]; several species of Liothrips are associated with similar damage to Piper vines, including commercial pepper crops, between southern India and northern Australia [19]. In South America, Holopothrips fulvus has been reported damaging the foliage of Cashew trees (Anacardium occidentale) [20], and Pseudophilothrips adisi is considered the key pest on cultivated Guarana (Paullinia cupana) [21].…”
Section: The Diversity Of Pest Thysanopteramentioning
confidence: 99%